PENGARUH MODEL MEANINGFUL INSTRUCTIONAL DESIGN (MID) TERHADAP MINAT BELAJAR DAN HASIL BELAJAR DALAM PEMBELAJARAN MENULIS PUISI - Nuriah, Neneng Siti; Hamdani, Agus; Novita, Lia (Jurnal Kata : Bahasa, Sastra, dan Pembelajarannya, 2023)
The purpose of this study is to determine the influence of the Meaningful Instructional Design (MID) model on learning interest and learning outcomes in learning to write poetry in grade X MA IPS Al-Barokah students for the 2022/2023 academic year. This research will be conducted from April 2023 to June 2023 at MA Al-Barokah. The research method used was quasi-expremin with a population of class X IPS MA Al-Barokah, as many as 2 classes with a total of 48 students. To measure students' interest in learning, instruments in the form of learning interest questionnaires totaling 20 questions and observation sheets totaling 15 statements were used. To measure learning outcomes, a test instrument is used in the form of questions in the form of poetry writing tasks, the data analysis technique used with the help of SPSS version 23. Based on the results of data processing from the test results using the Mann_Whitney test, the Asymp.Sig value is obtained. (2-tailed) of 0.000. So it can be concluded that there is an influence of the Meaningful Instructional Design (MID) model on learning interest and learning outcomes in learning to write poetry in Students in Class X MA Al Barokah Malangbong Academic Year 2022-2023. Tujuan penelitian ini adalah untuk mengetahui pengaruh model Meaningful Instructional Design (MID) terhadap minat belajar dan hasil belajar pembelajaran menulis puisi pada siswa kelas X MA IPS Al-Barokah tahun pelajaran 2022/2023. Penelitian ini dilaksanakan pada bulan April 2023 sampai dengan Juni 2023 di MA Al-Barokah. Metode penelitian yang digunakan adalah quasi-expremin dengan populasi siswa kelas X IPS MA Al-Barokah sebanyak 2 kelas dengan jumlah siswa 48 orang. Untuk mengukur minat belajar siswa digunakan instrumen berupa angket minat belajar berjumlah 20 soal dan lembar observasi berjumlah 15 pernyataan. Untuk mengukur hasil belajar digunakan instrumen tes berupa soal berupa tugas menulis puisi, teknik analisis data dengan bantuan SPSS versi 23. Berdasarkan hasil pengolahan data dari hasil pengujian menggunakan uji Mann_Whitney diperoleh nilai Asymp.Sig. sebesar 0,000. Simpulannya adalah terdapat pengaruh model Meaningful Instructional Design (MID) terhadap minat belajar dan hasil belajar pembelajaran menulis puisi pada Siswa Kelas X MA Al Barokah Malangbong Tahun Pelajaran 2022-2023.